Correlation Between Quadriceps-Hamstring Muscle Strength Ratio and Knee Joint Stability in Female Futsal Athletes - Rolina Manata BN; Nabil Rasya Habibi; Siti Mulya Ningsih; Muhammad Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Universitas Pendidikan Mandalika, 2026)
Knee joint stability is a crucial determinant of performance and injury prevention in professional futsal athletes who frequently perform explosive maneuvers. Muscle strength imbalance between the quadriceps and hamstrings has been identified as one of the major risk factors for functional instability. This study aimed to analyze the correlation between the quadriceps-hamstring muscle strength ratio (Q:H Ratio) and dynamic knee joint stability in professional female futsal athletes.The study employed a cross-sectional design involving 24 professional female futsal athletes. Muscle strength was measured using an isokinetic dynamometer to obtain peak torque values at an angular velocity of 60°/second, while dynamic stability was assessed using the Y-Balance Test (YBT). Descriptive statistical analysis showed that the mean Q:H ratio of the participants was 0.57 ± 0.05, which was below the ideal threshold (0.60). Pearson correlation analysis revealed a significant positive relationship with moderate strength between the Q:H ratio and the composite dynamic stability score (r = 0.612; p = 0.002). These findings indicate that the more balanced the strength between agonist and antagonist muscles, the better the resulting knee joint stability. In conclusion, the Q:H ratio is an important predictor of functional knee stability in futsal athletes. It is recommended that strength and conditioning coaches integrate eccentric hamstring strengthening programs to achieve an optimal strength ratio and reduce the risk of non-contact injuries.